2015
DOI: 10.1017/cem.2015.29
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian National EMS Research Agenda: Impact and Feasibility of Implementation of Previously Generated Recommendations

Abstract: Background: A recent mixed-methods study on the state of emergency medical services (EMS) research in Canada led to the generation of nineteen actionable recommendations. As part of the dissemination plan, a survey was distributed to EMS stakeholders to determine the anticipated impact and feasibility of implementing these recommendations in Canadian systems. Methods: An online survey explored both the implementation impact and feasibility for each recommendation using a fivepoint scale. The sample consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Studies on the dissemination of recommendations towards professionals are extensively described in the literature (e.g. [ 7 12 ]). However, it is not systematically investigated which strategies are feasible for the dissemination of recommendations to patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the dissemination of recommendations towards professionals are extensively described in the literature (e.g. [ 7 12 ]). However, it is not systematically investigated which strategies are feasible for the dissemination of recommendations to patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2015 Canadian Research Agenda for EMS research, most strengths, opportunities, barriers, and recommendations pertained to funding, time for doing research, and organizational culture [ 12 ]. Likewise, the 2003 USA research agenda addresses five major impediments for the performance of high-quality EMS research in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…However, an indepth analysis of current opportunities and barriers for performing research in EMS was not explored. Initiatives from other countries (e.g., Canada) have shown that a focus on opportunities and barriers can be extremely instrumental when it comes to setting priorities for research and improving the basic conditions needed for effective EMS research [11][12][13]. We hypothesize that this will also be true for the Netherlands.…”
Section: Introductionmentioning
confidence: 92%
“…Despite some relationship difficulties, most papers reported a general acceptance of the important role that regulation plays in terms of enhanced standards of practice, public safety and the reassurance and trust that regulation confers on professions [72,73]. This positive perspective is lent support by two papers studying professions not yet regulated, naturopathy [74] and massage therapy, which conclude that regulation would benefit public, practitioners and profession alike [75].…”
Section: Relations With the Regulatory Bodymentioning
confidence: 99%